2008
DOI: 10.1007/s11845-008-0172-9
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and perinatal outcomes after assisted reproduction: a comparative study

Abstract: Multi-foetal gestations remain the principal cause of adverse perinatal outcomes after ART. Singleton ART pregnancies have an increased risk of preterm delivery and low birth weight at term. Non-lethal congenital malformation rates are not increased following ART. Placenta praevia is increased following ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 52 publications
(60 reference statements)
3
28
0
3
Order By: Relevance
“…A large study of data obtained from three births registries in Western Australia revealed an increased incidence of congenital malformations in children born after IVF/ ICSI compared to children conceived naturally [19]. In addition, in a questionnaire-based comparative study (ART group versus the general population), singleton ART pregnancies had an increased risk of preterm delivery and low birth weight at term, but non-lethal congenital malformation rates were not increased following ART [20]. Moreover, a [1 -6] systematic review on the prevalence of birth defects in infants conceived after IVF/ ICSI versus spontaneously conceived infants had noted that two-thirds of the identified studies showed a 25% or greater increased risk of birth defects in the former group [21].…”
Section: Discussionmentioning
confidence: 99%
“…A large study of data obtained from three births registries in Western Australia revealed an increased incidence of congenital malformations in children born after IVF/ ICSI compared to children conceived naturally [19]. In addition, in a questionnaire-based comparative study (ART group versus the general population), singleton ART pregnancies had an increased risk of preterm delivery and low birth weight at term, but non-lethal congenital malformation rates were not increased following ART [20]. Moreover, a [1 -6] systematic review on the prevalence of birth defects in infants conceived after IVF/ ICSI versus spontaneously conceived infants had noted that two-thirds of the identified studies showed a 25% or greater increased risk of birth defects in the former group [21].…”
Section: Discussionmentioning
confidence: 99%
“…Allen et al [19], reported that singleton ART pregnancies have an increased risk of preterm delivery and low birth weight at term. Non-lethal congenital malformation rates are not increased following ART.…”
Section: Discussionmentioning
confidence: 99%
“…Use of drugs to cause superovulation has caused the vast majority of the increase in the multiples. (5, [18][19][20][21].…”
Section: Fertility Drugs and Assisted Reproductivementioning
confidence: 99%